PHE1-based IgG-like antibody platform provides a novel strategy for enhanced T-cell immunotherapy - Wang, Lingbin; Jiang, Haojie; Yin, Xuying; Liang, Tingting; Li, Guoming; Ding, Chen; Yang, Mina; Zhang, Lin; Liu, Junling; Xu, Yanyan (Frontiers in Immunology, 2024)
Bispecific antibodies (BsAbs) can simultaneously target two epitopes of different antigenic targets, bringing possibilities for diversity in antibody drug design and are promising tools for the treatment of cancers and other diseases. Here, we present a novel bsAb platform named PHE-Ig technique to promote cognate heavy chain (HC)-light chain (LC) pairing by replacing the CH1/CL regions of different monoclonal antibodies (mAbs) with the natural A and B chains of PHE1 fragment of Integrin β2 based on the knob-in-hole (KIH) technology. T-cell engaging bsAb is an important application of the bispecific antibody, which could promote T cell-mediated tumor cell killing by targeting tumor-associated antigen (TAA) and CD3 at the same time. We had verified that PHE-Ig technology can be effectively used as a platform to synthesize different desired bsAbs for T-cell immunotherapy. Especially, BCMA×CD3 PHE-Ig bsAbs exhibited robust anti-multiple myeloma (MM) activity in vitro and in vivo. Moreover, PHE1 domain was further shortened with D14G and R41S mutations, named PHE-S, and the PHE-S-based BCMA×CD3 bsAbs also showed anti BCMA+ tumor effect in vitro and in vivo.